The Association Between Maternal Shaking Behavior and Inappropriate Infant Parenting: The Japan Environment and Children's Study - Sakakihara, Aya; Masumoto, Toshio; Kurozawa, Youichi (Frontiers in Public Health, 2022)
Background: Although many studies have identified risk factors for maternal shaking behavior, it is unknown whether mothers who have shaken their infants repeat shaking behavior or show other inappropriate parenting behaviors. Using data from the Japan Environment and Children’s Study (JECS) birth cohort study, we investigated the associations between continuous shaking behavior and the associations between shaking behavior and other inappropriate parenting behaviors. Methods: JECS data starting from 2011 were used. Logistic regression was used to perform a cross-sectional analysis. The independent variable was shaking behavior and the dependent variables were leaving the infant home alone and hitting the infant (both at 1 month postpartum), and non-vaccination and infant burns (both at 6 months postpartum). A longitudinal analysis using logistic regression was also performed; here the independent variable was shaking behavior at 1 month postpartum and the dependent variables were shaking behavior, non-vaccination of the infant, and infant burns (all at 6 months postpartum). Results: In this study, 16.8% and 1.2% of mothers reported shaking behavior at 1 month and 6 months postpartum, respectively. Mothers who shook their infants at 1 month postpartum were approximately five times more likely to shake them at 6 months postpartum compared with mothers who had not shown previous shaking behavior (OR=4.93, 95% CI [4.23, 5.73], p < 0.001). In Cross-sectional study, there were associations between shaking behavior and inappropriate parenting behavior such as hitting the infant and infant burns. Conclusion: The findings suggest that mothers who report early shaking behavior tend to subsequently repeat this behavior, and that shaking behavior may be associated with other inappropriate parenting behaviors.